2011
DOI: 10.1175/2011jamc2632.1
|View full text |Cite
|
Sign up to set email alerts
|

Do Biometeorological Indices Improve Modeling Outcomes of Heat-Related Mortality?

Abstract: Various biometeorological indices and temperature measures have been used to assess heat-related health risks. Composite indices are expected to assess human comfort more accurately than do temperature measures alone. The performances of several common biometeorological indices and temperature measures in evaluating the heat-related mortality in Brisbane, Australia-a city with a subtropical climate-were compared. Daily counts of deaths from organic causes [International Statistical Classification of Diseases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
68
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 49 publications
(73 reference statements)
8
68
1
Order By: Relevance
“…Similarly, increasing specific humidity was also found to be more dangerous at high temperatures (Barreca, 2009). These results contrast with those for Australia (Vaneckova et al, 2011) and the United States (Barnett et al, 2010), where humidity was found to have little to no added effect on temperature-related health outcomes. Montero et al (2012) suggested temperature and 21 humidity associations should be analyzed separately, acknowledging that humidity may display negative and positive relationships with mortality for hot-dry and warm-humid climate settings, respectively.…”
Section: Humidity and All-cause Mortality And Morbiditycontrasting
confidence: 84%
See 1 more Smart Citation
“…Similarly, increasing specific humidity was also found to be more dangerous at high temperatures (Barreca, 2009). These results contrast with those for Australia (Vaneckova et al, 2011) and the United States (Barnett et al, 2010), where humidity was found to have little to no added effect on temperature-related health outcomes. Montero et al (2012) suggested temperature and 21 humidity associations should be analyzed separately, acknowledging that humidity may display negative and positive relationships with mortality for hot-dry and warm-humid climate settings, respectively.…”
Section: Humidity and All-cause Mortality And Morbiditycontrasting
confidence: 84%
“…Humidity plays a more noticeable role in increasing mortality in "cold compared to warm counties" in the United States, suggesting that adaptation may be important in moderating the climate and health relationship (Barreca, 2012). The lack of any humidity effects in Brisbane, Australia (Vaneckova et al, 2011) may be related to acclimatization or adaptation of the population to the warm humid climate there.…”
Section: Humidity and All-cause Mortality And Morbiditymentioning
confidence: 99%
“…The authors of that study did not find any significant differences between the usage of simple air temperature characteristics and biometeorological indices, and state that the selection of the mortality predictor is much less important than some other tasks. Daily mean temperature is an equivalent alternative, and in the case of an evaluation of heat-related mortality it shows similar results as various biometeorological indices according to other studies as well (Kim et al, 2011;Vaneckova et al, 2011). Urban and Kyselý (2014) also confirmed this finding in Central Europe when evaluating heat effects on cardiovascular mortality in the neighbouring Czech Republic.…”
Section: Fig 1: Location Of Climate Stations and Population Density supporting
confidence: 76%
“…Agam et al, 2008;Kalma et al, 2008;Anderson et al, 2011Anderson et al, , 2012, emergency responses to heat waves (e.g. Endlicher et al, 2008;Tong et al, 2012;Vaneckova et al, 2011;Zanobetti et al, 2012), infectious disease control (e.g. Reisen et al, 2006;Midekisa et al, 2012), lake ecology (e.g.…”
Section: Recommendation 3: Demonstrate New Underpinning Applications mentioning
confidence: 99%